Efficiency of face milling hardened steels with cubic boron nitride tools - V.S. Antonyuk (Технічна інженерія)
Face milling of hardened steels is an important process in modern mechanical engineering, as it allows achieving high precision and quality of machined surfaces of machine parts. With the development of technology and materials science, new tool materials have emerged that significantly enhance machining efficiency. One such material is cubic boron nitride (CBN), which, due to its unique properties, has become indispensable in many industries. CBN is the second hardest material after diamond, making it suitable for machining hard materials such as hardened steels. The high thermal stability and chemical inertness of CBN allow its use in high-temperature and aggressive environments, significantly increasing tool productivity and longevity. Additionally, CBN tools provide high surface quality, reducing roughness and improving the accuracy of machining flat surfaces. This article examines the efficiency of using cubic boron nitride tools in face milling of hardened steels. Analytical studies were conducted to evaluate the impact of different cutting regimes on the quality of the machined surface of hardened steel and the wear resistance of the tool. The analysis results show that CBN tools ensure high machining accuracy and reduced surface roughness, making them effective for machining high-hardness hardened steels. The article also discusses the economic aspects of using CBN tools in industrial conditions. The high cost of CBN tools is offset by their durability and high productivity, ultimately reducing overall machining costs. Thus, the use of cubic boron nitride tools is a promising direction for improving the efficiency and quality of machining hardened steels.